Pengaruh Terapi Okupasi terhadap Kemampuan Sosial pada Klien Skizofrenia dengan Isolasi Sosial - Rendra Sukmana; Nawang Wulandari (Journal of Ners and Midwifery, 2014)
Occupational therapy is a healing effort against someone who is experiencing mental and physical disorders by giving liveliness job. The purpose of the study to determine the effect of Occupational Therapy on social skills in schizophrenia with social isolation, using Quasy Control Group Pre-test Posttest Design. Sampel used in this experiments were 10 respondents that are divided into 2 groups: treatment and control. The treatment group was given occupational therapy 2 times a week for 3 weeks. Observations by 12 questions was conducted to determine the level of social skills of respondents. The results of this study showed no increase on the level of social skills before and after given granted Occupational Therapy. The level of social capability of 5 respondents in the treatment group before given an Occupational Therapy were 7 and while after given an occupational therapy were 10.2. This result have contrast to the control group which showed level of social capability were 7 . Statistic Analized using Wilcoxon Sign Rank Test showed significant is 0.0205 in the group between pre and post treatment, while the treatment and control group comparisons with Mann Whitney U test showed 0.029 â‰¤ 0.05. With these results Occupational Therapy can improve social skills clients with social isolation.